1996
DOI: 10.5006/1.3292084
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Surface Changes During Ennoblement of Type 316L Stainless Steel: Dissolved Oxidant and Capacitance Measurements

Abstract: Ennobled open-circuit potential (E corr ) for type 316L stainless steel (SS [UNS S31603]) exposed to fresh river water was investigated using microelectrodes to measure dissolved oxygen (DO), hydrogen peroxide (H 2 O 2 ), and local E corr within biofouling deposits. Galvanostatic techniques were used to measure capacitance (C) and to titrate reducible surface material. Results indicated deposits were uniformly aerobic and did not contain elevated levels of cathodic depolarizers. Development of ennobled potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 3 publications
1
14
0
1
Order By: Relevance
“…Then, the current density variation is one order magnitude lower for oxidized AISI 316L specimens compared to blank specimens. Our results are in accordance with the literature which shows that preoxidation of the AISI 316L improves its aqueous corrosion resistance for biomedical applications [19][20][21][22][23][24][25][26][27][28][29][30][31][32]. In this case the objective is to avoid the hexavalent chromium release from the AISI 316L stainless steel implants [33].…”
Section: Role Of Molybdenumsupporting
confidence: 94%
See 1 more Smart Citation
“…Then, the current density variation is one order magnitude lower for oxidized AISI 316L specimens compared to blank specimens. Our results are in accordance with the literature which shows that preoxidation of the AISI 316L improves its aqueous corrosion resistance for biomedical applications [19][20][21][22][23][24][25][26][27][28][29][30][31][32]. In this case the objective is to avoid the hexavalent chromium release from the AISI 316L stainless steel implants [33].…”
Section: Role Of Molybdenumsupporting
confidence: 94%
“…However, in situ X-ray diffraction (XRD) studies have never been performed on AISI 316L specimens at 800°C in order to check if a change in the structural composition of the layer appears with time and if oxide phase transitions occur during cooling to room temperature as it was demonstrated on a AISI 304 substrate [18]. From the literature, it appears that pre-oxidation of the AISI 316L SS has been tested in order to improve its aqueous corrosion resistance [19][20][21][22][23][24]. A general corrosion improvement of this material was also obtained for biomedical applications [25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Herzberg et al (2010) reported the thicknesses of biofilms formed at 25°C from treated sewage as between 82.3 ± 31.7 μm after 8.5 days. Similarly, Dickinson et al (1996) reported that biofilms of Aeromonas sp. formed on SS316 from river water at its ambient temperature reached thicknesses of 2-40 ± 5 μm after 35 days.…”
Section: The Thickness Of the Fouling Layer And Thermal Resistancementioning
confidence: 95%
“…It is also important to mention that full colonization of the stainless steel coupons is not a prerequisite for stainless steel ennoblement. Dickinson et al [48] found that development of increased potential occurred on surfaces with as little as 3–5% biofouling coverage. Some researchers [41,43,48–50] already performed in situ biological experiments with non‐welded stainless steel coupons where ennoblement was observed, but no real evidence of corrosion features (e.g.…”
Section: Discussionmentioning
confidence: 99%